The Teachers' Creativity in Implementing of 2013 Curriculum through Discovery Learning Model in English Subject at SMP Negeri 3 Bantan - Ruzaini Ruzaini; Rini Fitria (STAIN Bengkalis, 2021)
The background of this research is that the teacher as a professional educator is not enough to only master the knowledge that supports it, it is also agreed to be demanded to understand the students. Because teachers are needed who are inspiring, creative, able to educate, provide a good attitude, and understand students' mentality. The problems with this research are teachers’ creativity through the discovery learning model and implementation of the 2013 curriculum in SMP Negeri 3 Bantan. This research method is descriptive quantitative. Quantitative data were obtained at 72,59%. This value is qualitatively based on the creativity of teachers in implementing the 2013 curriculum through the learning model of discovery in English subjects in SMP Negeri 3 Bantan which is categorized as sufficient, this is related to that number in the range of grades of 56% - 75% according to the standards used in this study. The implementation of the 2013 curriculum at SMP Negeri 3 Bantan has begun from the 2016/2017 school year. Implementation of the 2013 curriculum is also supported by several factors, namely teacher readiness, facilities and infrastructure, and input from students. The school also provides standards for teachers to implement 5M in every teaching and learning process. The 5M (mendukung, menanya, menganalisis, mencoba, and mengkomunikasikan) is supporting, asking, analyzing, trying, and communicating.